2019
DOI: 10.1111/tpj.14462
|View full text |Cite
|
Sign up to set email alerts
|

Positional differences of intronic transposons in pAMT affect the pungency level in chili pepper through altered splicing efficiency

Abstract: Summary Capsaicinoids are unique compounds that give chili pepper fruits their pungent taste. Capsaicinoid levels vary widely among pungent cultivars, which range from low pungency to extremely pungent. However, the molecular mechanisms underlying this quantitative variation have not been elucidated. Our previous study identified various loss‐of‐function alleles of the pAMT gene which led to low pungency. The mutations in these alleles are commonly defined by Tcc transposon insertion and its footprint. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…chromosome-level assembly, GC content, genome assembly, Hi-C, long reads, satellite repeat, transposable element four-stranded DNA/RNA topologies that seem to be involved in numerous cellular processes, such as regulation of gene expression (Du, Zhao, & Li, 2008Raiber et al, 2011), genetic and epigenetic stability (Schiavone et al, 2014), and telomere maintenance (Biffi et al, 2012). On the repetitive element side, for example, transposable elements are a major target of epigenetic silencing (Law & Jacobsen, 2010) that may influence the epigenetic regulation of nearby genes (Chuong et al, 2016;Cowley & Oakey, 2013;Tanaka et al, 2019). The epigenetic effect of individual TE insertions may be beneficial or deleterious, but in either case it is important to acknowledge their overall effect on the evolution of gene expression (Lerat et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…chromosome-level assembly, GC content, genome assembly, Hi-C, long reads, satellite repeat, transposable element four-stranded DNA/RNA topologies that seem to be involved in numerous cellular processes, such as regulation of gene expression (Du, Zhao, & Li, 2008Raiber et al, 2011), genetic and epigenetic stability (Schiavone et al, 2014), and telomere maintenance (Biffi et al, 2012). On the repetitive element side, for example, transposable elements are a major target of epigenetic silencing (Law & Jacobsen, 2010) that may influence the epigenetic regulation of nearby genes (Chuong et al, 2016;Cowley & Oakey, 2013;Tanaka et al, 2019). The epigenetic effect of individual TE insertions may be beneficial or deleterious, but in either case it is important to acknowledge their overall effect on the evolution of gene expression (Lerat et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Technological biases are therefore impeding the 67 complete reconstruction of genomes and substantial regions are systematically missing from genome 68 assemblies. These missing regions are often referred to as the genomic "dark matter" (Johnson et al 69 for example, transposable elements are a major target of epigenetic silencing (Law and Jacobsen 122 2010) that may influence the epigenetic regulation of nearby genes (Cowley and Oakey 2013;Chuong 123 et al 2016; Tanaka et al 2019). The epigenetic effect of transposable elements may be beneficial or 124 deleterious, but in either case it is important to acknowledge their potential involvement in the 125 evolution of gene expression (Lerat et al 2019).…”
mentioning
confidence: 99%
“…For example, Pun1 is the most downstream gene in the capsaicinoid biosynthesis pathway, and functional loss of Pun1 due to mutation prevents capsaicinoids synthesis (Stewart et al, 2005). As a result, functional loss of CaMYB31 and pAMT also caused the loss of, or drastic reduction in, pungency (Han et al, 2019;Tanaka et al, 2019). Moreover, it was reported that gene silencing of Pun1, pAMT, KAS, and CaMYB31 using virus-induced gene silencing (VIGS) caused dramatic decreases in capsaicinoid contents (Abraham-Juárez et al, 2008;Ochoa-Alejo, 2015, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Above all, Pun1, which encodes an acyltransferase, is one of the most critical genes in capsaicinoid biosynthesis and is responsible for the final reaction in the pathway (Stewart et al, 2005(Stewart et al, , 2007. Then, putative aminotransferase (pAMT), which produces vanillylamine from vanillin, is also important and mutation of this gene caused a drastic reduction in capsaicinoids (Koeda et al, 2014;Lang et al, 2009;Tanaka et al, 2010Tanaka et al, , 2019. Furthermore, in recent years two novel genes were discovered that induced loss of pungency.…”
Section: Introductionmentioning
confidence: 99%